The Relationship Between Psychological Symptoms, Creativity, and Loneliness in Gifted Children - Ogurlu, Uzeyir; Yalin, Hatun Sevgi; Birben, Fazilet Yavuz (SAGE PUBLICATIONS INC, 2018)
The aim of this study was to examine the relationship between psychological symptoms, creativity, and loneliness among gifted middle school students and to analyze gender difference in psychological symptoms. The study used a correlational design, consisting of 91 gifted middle school students. The Brief Symptom Inventory, the University of California, Los Angeles (UCLA) Loneliness Scale, and the Torrance Tests of Creative Thinking were used as data-collection instruments. The results showed that there was no significant difference between gifted female and male students in the Brief Symptom Inventory total score and subscales except in the depression subscale. In addition, the Brief Symptom Inventory including subscales was significantly and positively correlated with the UCLA Loneliness Scale. There was no significant correlation between the Torrance Tests of Creative Thinking and the other scales. Loneliness was found to be a significant predictor of psychological symptoms. The results of this study suggest that loneliness is a major factor for the psychological well-being of gifted students.
Keywords: gifted students; psychological symptoms; creativity; loneliness; ADJUSTMENT PROBLEMS; SUICIDE IDEATION; MENTAL-ILLNESS; STUDENTS; DEPRESSION; ADOLESCENTS; PERSONALITY; PSYCHOPATHOLOGY; COMPETENCES; DISORDERS; Education & Educational Research